Prognostic value of transthoracic echocardiography and BNP as a biomarker of cardiac dysfunction in COVID-19 and non COVID-19 pneumonia patients admitted to intensive care units. (Cuestiones de Fisioterapia, 2025)
Background: One of the main reasons for hospitalization is community-acquired pneumonia (CAP), and about 10% of hospitalized CAP patients need ICU admission which also causes high rates of morbidity, mortality , and medical expenses. The most important aspects of managing CAP patients are risk classification and prognosis prediction, which enable the choice of the best care environment, including outpatient therapy, hospital ward admission, or the critical care unit.